PHOTOCATALYST: A PROMISING SMART MATERIAL IN DEGRADATION OF DYE USING RESPONSE SURFACE METHODOLOGY (RSM (FUDMA JOURNAL OF SCIENCES, 2020)
One of the environmental issues is water Pollution causing serious health related problem not only to human but also seriously affect aquatic life. Dyes are among the pollutants that pollute our water bodies. In the olden days so many methods were applied for the purification of water but recently photocatalysis shown a promising technique where the pollutants (dyes) were degraded to give clean water and carbon dioxide to be liberated as the end product. The specific surface area of the photocatalyst 243.80 m2g-1 and the PZC was found to be 8.10. Only 0.9% of the dye (MG) decolorized in the presence of light (photolysis) while 25% of the MG was adsorbs in the dark with 30 minutes of contact. The ANOVA showed an F-value of 1114.81 which suggests that the model is significant. All model terms i.e. MG initial concentration, photocatalyst dose, irradiation period and pH are all significant with Prob>â€ values
Keywords: Malachite green (MG), Point of Zero charge (PZC), Dye, ZnFe2O4 / TiO2 composite, CCD